Influencia de la comunicación online en las relaciones interpersonales de los habitantes del Recinto San Francisco, cantón Ventanas, año 2021 - Manrique Moran, Leonardo Fernando (2021)
Online communication in today's society is widely used in different ways, whether to communicate, entertain or exchange ideas, it is very useful and it is interactive, efficient and fast. In the world, online communication is gaining strength, with great breadth it could already be said that it has become one of the largest and indispensable sources and integrating means of an entire society. The way we relate to others, the way we express our ideas and thoughts or opinions, become more evident and more frequently due to digital communication and the constant use of it. This type of communication creates a number of situations, including interpersonal relationships, which is why, in our research work, this issue is encountered, in which it encompasses all of this, for the following reason for our study we conducted 30 surveys to the inhabitants where we carry out the research, for which, in the following pages, you will learn about the exhaustive and investigative work on the influence of online communication on interpersonal relationships.